Flow cytometry combined with viSNE for the analysis of microbial biofilms and detection of microplastics - Linn Sgier (Nature Portfolio, 2016)
The interpretation of high-dimensional flow cytometry data is difficult and time consuming. Here, Sgier et al.present an improved method that combines stain-free flow cytometry with viSNE data visualization for the analysis of microbial biofilms.